2019
DOI: 10.4238/gmr18305
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Novel selection strategy for half-sib families of sour passion fruit <i>Passiflora</i> <i>edulis</i> (Passifloraceae) under recurrent selection

Abstract: Several strategies have been employed in the breeding of passion fruit with a view to the generation of superior progeny. In an effort to develop more precise methods in breeding, we compared the efficiency of the Post-Hoc Blocking Row-Col technique, which is an a posteriori technique that consists of the overlapping of a block structure on the original-field design, with a randomized-block design and compared different selection strategies within and among half-sib families, using the REML/BLUP mixed-model me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
1
8
0
2
Order By: Relevance
“…These estimates presented values within the expected range for these traits, considering they are controlled by a large number of genes and are highly influenced by the environment (Resende et al, 2014). Cavalcante et al (2019) found similar estimates for the same crop. Viana et al (2004) evaluated the same variables in passion fruit and found higher heritability estimates for all variables except TSS, indicating a favorable situation for selection.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…These estimates presented values within the expected range for these traits, considering they are controlled by a large number of genes and are highly influenced by the environment (Resende et al, 2014). Cavalcante et al (2019) found similar estimates for the same crop. Viana et al (2004) evaluated the same variables in passion fruit and found higher heritability estimates for all variables except TSS, indicating a favorable situation for selection.…”
Section: Resultsmentioning
confidence: 55%
“…Passiflora edulis is the most marketable passion fruit species in Brazil, accounting for more than 95 % of the fruit farms in the country and also the most planted species worldwide (Meletti et al, 2011). Passion fruit production in the state of Rio de Janeiro is below the national average, mainly due to the lack of improved varieties adapted to edaphoclimatic conditions; however, breeding programs are working to improve this condition (Cavalcante et al, 2019). In passion fruit, breeding methods face challenges similar to other perennial species.…”
Section: Introductionmentioning
confidence: 99%
“…However, production has been decreasing since 2013, with a 28.95% decrease in 2019. This decline is caused by several factors, including phytosanitary problems and the lack of genotypes adapted to the growing regions (Silva et al, 2009;Cavalcante et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…O maracujá (Passiflora edulis Sims) é uma das culturas de maior relevância comercial, constituindo 95% dos pomares no país, gerando emprego e renda em diversos municípios (IBGE, 2019;Cavalcante et al, 2019). Nesse contexto, o Brasil se destaca como o maior produtor e consumidor mundial de maracujá, produzindo 593.429 toneladas, em 41.584 ha, dos quais 64,5% da produção corresponde a região Nordeste (IBGE, 2019).…”
Section: Introductionunclassified